PELATIHAN PEMBUATAN ALAT PERAGA MESIN STIRLING UNTUK GURU FISIKA SMA - Yantidewi, Meta; Prastowo, Tjipto; Deta, Utama Alan (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2018)
Â Physics is a part of sciences that underlies the development of advanced technology and the concept of living in harmony with nature. In physics learning, conceptual understanding with direct learning experience might be able to carry out through experimental or practicum activities by utilizing practicum tools in the Physics Laboratory of school and also by holding out some demonstrations during class. The development of thermophysical practicum tools and the arrangement of related student workbook (LKS) are mainly purposed to improve the pedagogical and profession competence of high school physics teachers who are members of MGMP Fisika SMA Dinas Pendidikan Kabupaten Bojonegoro, to be accustomed and skillful to make and use of high school physics learning which is simple and can support high school physics learning. The training activities by the 2017 PKM Team are carried out in three stages: designing, manufacturing of thermophysical practicum tools, and comprehensive evaluations. This activity is expected to increase the pedagogical and profession competence high school physics teachers of Kabupaten Bojonegoro, especially in the manufacture of media and practicum visual This activity is expected to increase the competence of pedagogy and profession of high school physics teachers of Bojonegoro Regency, especially in the manufacture of media and visual practicum visuals as well as a form of teaching a physics-based approach to a scientific approach. Workshop activities are planned to be followed by several high school physics teachers of Bojonegoro Regency. The time of the workshop is on Saturday 21st of October 2017. The average performance of the trainees this time has been very good. The participants' responses to this activity are also very good. Evident from the performance test sheet and training participants 'responses indicating that 70% of the participants had excellent performance and more than 70% of participants stated that the event was excellent in supporting students' understanding of the thermophysical material, especially Stirling Machine.